(untitled) (Applied Biological Research, 2018)
The evolutionary distances from an individual to other individuals of the same plant species were mapped in geographical information system (GIS). To do this, the relationship between the intraspecies evolutionary distances and the bioclimatic, geographic and elevation distances were determined for 17 plant species through multiple linear regression (MLR). Evolutionary distances were calculated by constructing Neighbor-joining and Maximum likelihood-based phylogenetic tree. Power, inverse-power, log10 and Box-Cox transformations were used for both evolutionary and environmental distances. The use of bioclimatic, geographic and elevation predictors and power transformation for MLR models resulted in explaining more than 60% of variation in intraspecies evolutionary distances for 12 plant species. Power transformation method was more effective than other methods for increasing models R2. Comparison of MLR and distance-based redundancy analysis (db-RDA) indicated the efficiency of MLR in predicting intraspecies evolutionary distances based on environmental distances.